Eyes do not lie. Investigation of the effectiveness of outdoor advertising instruments: an applied neuromarketing research with eye-tracking technique - Şik, Eser; Soba, Mustafa (Acta Bioethica, 2021)
Traditional techniques of market research and information gathering to meet business needs fail because they cannot always produce the desired results. This has necessitated the use of new techniques and methods for gathering information. Companies frequently resort to advertising activities for the promotion of a new product or to increase sales of an existing product and want to be compensated for the expenses incurred in these activities. It is necessary to measure the effectiveness of advertising in order to know how the response to the advertisement is after its publication. A questionnaire and an eye tracker were applied to 32 participants to investigate the communication effectiveness of 25 outdoor advertisements. As a result, it is obtained that the survey method is not fully sufficient to provide the real data needed by the company. The recognition method reflects the truth: real data can be obtained from the participants with the neuromarketing method and it has been determined that the company can achieve the real data it needs.